Rancang Bangun Aplikasi Penilaian Kinerja Guru Berbasis Website Menggunakan Metode Behaviorally Anchor Rating Scale (Studi Kasus : SMPN 26 Surabaya) - Hendri Prasetyawan; Titik Lusiani; Teguh Sutanto (Jurnal Sistem Informasi Universitas Dinamika, 2021)
SMPN 26 Surabaya is a junior high school established in the city of Surabaya, East Java. At SMPN 26 Surabaya, the teacher performance appraisal process carried out still does not refer to Permendiknas No. 35/2010 concerning teacher competence and academic standards so that it still follows the teacher performance appraisal criteria recommended by the principal directly. The performance appraisal that has been carried out does not yet have good teacher performance appraisal data archiving so that the principal or teacher often experiences not being able to see the results of the performance report. As a solution to the existing problems, a website-based teacher performance appraisal application was created which can help reduce processing time in the teacher performance appraisal process. The teacher performance appraisal process in the application will use the Behaviorally Anchor Rating Scale method and will use Permendiknas No. 35/2010 concerning teacher competence and academic standards. In the teacher performance appraisal that will be carried out will be assessed by the principal and senior teachers. Based on the results of the trial of each function in the system it shows that the teacher performance appraisal application by applying the Behaviorally Anchor Rating Scale Method at SMPN 26 Surabaya has been running well and the calculation results are good. corresponding. As well as being able to carry out assessments in accordance with the rules stipulated by No. 35 of 2010 concerning teacher competence and academic standards. In addition, the application can also provide a recap and report on teacher performance appraisals